Concordance in diabetic foot ulceration : a cross-sectional study of agreement between wound swabbing and tissue sampling in infected ulcers /: a cross-sectional study of agreement between wound swabbing and tissue sampling in infected ulcers. (November 2016) - Nelson, E. A (E. Andrea)
No abstract available